On the architecture of words. Applications of meaning studies - GODED RAMBAUD, Margarita et al. (Colección de libros electrónicos en Xebook, 2015)
In light of today's extensive use of digital communication, this volume focuses on how to understand and manage the various types of linguistically-based products that facilitate the use and extraction of information. Including conceptual and terminological databases, digital dictionaries, thesauri, language corpora, and ontologies, they all contribute to the development and improvement of language industries, such as those devoted to automatic translation, knowledge management, knowledge retrieval, linguistic data analysis, and so on. As the theoretical background underlying these applications is outlined in detail in the earlier chapters of the book, the reader is able to establish the necessary links between the various but related kinds of linguistic -and, in particular, semantic- applications. A general review of several theories and linguistic models that influence the practical application of Meaning studies to the new technologies is also included.